1995
DOI: 10.1029/95gl02950
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of the temperature profile between 25 and 103 km: Evidence of strong tidal perturbation

Abstract: Simultaneous observations of the middle atmosphere and lower thermosphere by Na Wind/Temperature (W/T) and Rayleigh/Raman lidar and other ground‐based measurements were conducted the night of October 21, during the ALOHA‐93 campaign. Rayleigh/Raman lidar measurements provide density from 25 to 90 km and temperature from 25 to 85 km. From the same location, Na W/T lidar measurements were also obtained between ∼83 and 103 km. The combined data provides continuous temperature from 25 to 103 km. Strong perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 5 publications
8
71
2
Order By: Relevance
“…The ranges of amplitudes for the (2,5) mode were based on values found previously to produce reasonable agreement with the ARIA I wind observations (Parish et al, 2003), and to be consistent with values measured in recent satellite and ground based observations (e.g. Hecht et al, 1998;Karpov 1996;Dao et al, 1995). In this example, the amplitude of the geopotential height variation of the (2,5) tidal mode in the background winds has been varied between 100 m and 300 m, for a tidal phase of 3.0 h LT, where propagating tides are forced at the lower boundary of the CTIP model at 80-km altitude.…”
Section: (25) Tidal Modesupporting
confidence: 87%
“…The ranges of amplitudes for the (2,5) mode were based on values found previously to produce reasonable agreement with the ARIA I wind observations (Parish et al, 2003), and to be consistent with values measured in recent satellite and ground based observations (e.g. Hecht et al, 1998;Karpov 1996;Dao et al, 1995). In this example, the amplitude of the geopotential height variation of the (2,5) tidal mode in the background winds has been varied between 100 m and 300 m, for a tidal phase of 3.0 h LT, where propagating tides are forced at the lower boundary of the CTIP model at 80-km altitude.…”
Section: (25) Tidal Modesupporting
confidence: 87%
“…The first was initially proposed by Whiteway et al (1995) and basically explains the formation of MIL by turbulent heating. The second goes back to Dao et al (1995) and was summarized e.g., by Meriwether and Gardner (2000) and explains the formation of a MIL via the interaction of tides with gravity waves. Both these scenarios are discussed in detail e.g., in the review article by Meriwether and Gerrard (2004).…”
Section: Discussionmentioning
confidence: 99%
“…2 one can see a downward phase progression of both MILs which is marked by the arrows. Using simple analysis e.g., applied by Dao et al (1995), that is by fitting a polynomial to the temperature profiles and looking on the temperature maxima, one can find that the upper MIL (86 to 89 km at the time of the rocket launch) descends approximately at a rate of 15 km per 12 h. The lower MIL descends with the same speed and is located ∼ 15 km below the upper one. Figure 3 shows temperature measurements obtained with the MLS over the rocket launch site close to the time of the ECOMA09 flight.…”
Section: Lidar Temperature Measurementsmentioning
confidence: 99%
“…Liu et al (2000) showed that breaking gravity waves can warm the air sufficiently for the formation of MILs if the static stability of the mesosphere had been decreased by a tidal wave. Models and observations have revealed that the upper MILs have an amplitude maximum during the winter at mid-latitudes (Dao et al, 1995;Liu et al, 2000;Meriwether et al, 1998). The occurrence of the lower MILs is a characteristic and persistent feature of the winter mesosphere and lower thermosphere (MLT) (Hauchecorne et al, 1987;Meriwether and Gardner, 2000).…”
mentioning
confidence: 99%